Strategies for Life Planning After Retiring from Sports for Thai National Wushu Athletes - Yangrungrawin, Sujinda (Journal of Dhamma for Life, 2025)
The objective of this research is to study” Strategies for Life Planning After Retirement from Sports of Thai National Wushu Athletes” aimed to (1) explore the post-retirement living conditions of Thai national wushu athletes, (2) examine the factors influencing life planning after retirement, and (3) propose strategies that athletes can adopt after their retirement from wushu sports. The research employed a qualitative approach, collecting data from ten participants comprising national wushu team executives and retired athletes. Research tools included document analysis and structured interviews focusing on post-retirement living conditions and factors influencing life planning. The findings were analyzed using content analysis and presented descriptively. The research findings revealed the following 1) After retiring from sports, Thai national wushu athletes experienced significant life changes across various dimensions, affecting their physical, mental, and financial well-being. Each dimension presented unique challenges requiring tailored solutions and appropriate support. 2) Factors influencing life planning after retirement included physical health, mental readiness, family and social support, personal financial management, and policies from sports organizations. 3) Proposed strategies for life planning focused on physical rehabilitation, psychological support, and financial stability. Comprehensive programs addressing these areas such as health recovery, setting new life goals, and developing career skills would enable athletes to adapt and build sustainable, stable lives post-retirement. If each factor is adequately addressed, athletes can transition effectively and achieve long-term quality of life.